Performance Analysis of the Soybean Agroindustry Supply Chain - Alfan T Afianto; Sukardi; Faqih Udin (International Journal of Engineering and Management Research, 2019)
Soybean is one of the primary commodities of food after rice and corn. Soybean in Indonesia is one of the strategic food crops. The problem of local soybean supply chain compared to the important soybean chain is the supply of local soybeans involving many parties in soybeans. The number of distribution channels for the supply of local soybeans is also a trend for changes in price variations. More effective than efficient and efficient supply chains in local soybeans. The objectives of this study are (1) to identify conditions and protection in the soybean supply chain; (2) Analyzing the performance of the soybean agroindustry supply chain. To analyze the investment supply chain using the Food Supply Chain Network (FSCN), SCOR-AHP is used to analyze supply chain performance. The structure of soybean agroindustry supply chain in Cianjur Regency involves farmer, breeder, collector, Indonesian Tofu and Tempe Producers Cooperatives (KOPTI), agro-industry, local traders and inter-regional traders. The results of the calculation of the valuation of the market at the farmer level are 85,325%, traders are 92,926%, and agroindustry is 87,004%.